EFFECT OF ENTREPRENEURIAL ORIENTATION ON BUSINESS PERFORMANCE OF MSMES IN CERME DISTRICT WITH TECHNOLOGY ADOPTION MEDIATION - Rossy Yudistira; Eko Wahjudi (Jurnal Industri Kreatif dan Kewirausahaan, 2025)
This research examines the influence of entrepreneurial orientation and technology adoption on the business performance of culinary sector MSMEs in Cerme District, Gresik Regency. The research employed a quantitative methodology. The sample consisted of 60 respondents, and the data analysis was conducted using path analysis with Structural Equation Modeling (SEM) based on Partial Least Squares (PLS), assisted by the WarpPLS 8.0 software. The results show that entrepreneurial orientation does not have a direct and significant effect on MSME business performance. However, entrepreneurial orientation has a significant effect on technology adoption, and technology adoption significantly affects business performance. Moreover, technology adoption is proven to significantly mediate the effect of entrepreneurial orientation on business performance. These findings emphasize the crucial role of technology adoption as a bridge between entrepreneurial understanding and improved MSME business performance. Therefore, MSME actors are expected not only to possess strong entrepreneurial characteristics but also to be able to adapt to technological developments as a strategy to enhance competitiveness and business sustainability.